GAMBARAN SERVICE EXCELLENT PADA PEGAWAI DI UNIVERSITAS HKBP NOMMENSEN MEDAN - Fredinan De Hotman Zebua; Hotpascaman Simbolon; Karina M Brahmana (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
The development of Science and Technology (IPTEK) currently requires better competition in advancing an organization, Higher Education (PT) is an organization that involves various elements, one of which is human resources (HR). Service quality will greatly determine the success of higher education in competing, excellence in competition between universities in the future will also be determined by the quality of service outside the classroom, in this case excellent service. The purpose of this study was to see an overview of excellent service to employees at Unversisty of HKBP Nommensen Medan. The sample in this study were students, totaling 380 people. The measuring instrument used in this research is one of the measuring tools, namely excellent service which is arranged in the form of a Likert scale. The research data were analyzed using descriptive tests with the help of SPSS 17.0 for windows. Where the results are excellent service at the University of HKBP Nommensen Medan which is in the medium category.